Single-center real-world data on the efficacy, safety, and current availability of pegylated interferon-α in hematologic neoplasms - Bahçecioğlu, Adile Begüm; Büyükaşık, Yahya (Acta Medica, 2026)
Aims: Pegylated interferon-α (PEG-IFN-α) offers improved pharmacokinetics compared with conventional interferon-α (IFN-α), yet real-world data on its clinical activity and safety across heterogeneous hematologic neoplasms are limited. This study aimed to evaluate the real-world efficacy, durability of response, and toxicity of PEG-IFN-α in patients with diverse hematologic neoplasms. Methods: This retrospective study evaluated the efficacy, duration of response, and toxicity of PEG-IFN-α using patient medical records and hospital electronic registries. Thirty patients were included: polycythemia vera (PV, n=12), essential thrombocytosis (ET, n=6), chronic myeloid leukemia (n=2), primary myelofibrosis (n=1), systemic mastocytosis (SM,n=3), hypereosinophilic syndrome (HES, n=1), Erdheim–Chester disease (ECD, n=4), and lymphomatoid granulomatosis (LYG, n=1). Results: PEG-IFN-α was initiated due to resistance to prior therapies in 12 patients (40%), intolerance or toxicity in 10 patients (33.3%), and as first-line treatment in 8 patients (26.7%). Among PV patients, a complete response was achieved in 41.6% and a partial response in 50%. In ET patients, 83.3% achieved a complete response, while 16.7% showed no response. All patients with SM demonstrated clinical improvement when PEG-IFN-α was used as first-line therapy. In ECD patients, follow-up PET imaging showed stable disease in two patients, partial response in one, and no response in one. Partial responses were also observed in patients with HES and LYG. Treatment-related toxicity occurred in 8 patients (26.6%) and led to treatment discontinuation in 6 patients (20%) (including cytopenias, influenza-like symptoms, and elevated liver enzymes). Conclusion: In this real-world cohort, PEG-IFN-α showed encouraging activity across several hematologic neoplasms, with toxicity and discontinuation rates in line with previously published series of conventional interferon-α; however, its clinical use remains limited by regulatory and access constraints.